Palavras complexas na aquisição da morfologia do Português: estudo de caso - Vigário, Marina (2017)
We investigate morphological development in the first productions of a child (L). Until de age 2, the large majority of L’s productive vocabulary is composed of simple (non-)inflected words, belonging to the Noun category (Verbs are much less frequent; Adverbs and words belonging to closed classes are residual). The consistent production of complex words appears at around 2;03, coinciding with a moment of lexical explosion. At about the same time Adjectives appear and Verbs and closed class words become increasingly frequent. Novel words coined by L (e.g., mimpazinha ‘limpinha’) appear roughly in the same period, showing that the child is already analysing words and applying morphological rules when the first complex words are consistently produced.